Nitroxides Theory, Experiment and Applications - Kokorin, Alexander I. (IntechOpen, 2012)
Nitroxide (aminoxyl) radicals became the start point for one of the most interesting and rapidly developing areas of modern chemical physics with valuable applications to biophysics, molecular biology, polymer sciences and medicine. This book, consisting of 15 chapters gathered in 3 sections, written by authors actively involved in the area of spin label/probe technique. The authors describe in detail some novel trends and analyze new approaches of practical applications of nitroxide radicals. The book, recommended by the Governing Council of N. Semenov International Center of Chemical Physics, Moscow, will be of help to many scientists: chemists, physical chemists, biophysicists, biologists, physicians and other experts in a variety of disciplines, in which spin labels and probes are used, as well as to students and PhD students. It may be also suitable for teaching, and may help to promote the progress in natural sciences.